The global role of Lrp in Vibrio alginolyticus and its response to diverse physicochemical factors - Su, Wenxiao; Deng, Yiqin; Zang, Shujun; Gao, Si’ao; Feng, Juan (Frontiers in Marine Science, 2022)
Leucine-responsive regulatory protein (Lrp) is an essential transcriptional regulator in prokaryotes. However, the regulatory role of lrp in Vibrio alginolyticus still lacks detailed research. In this study, an lrp mutant strain was constructed to gain insight into the global role of lrp in Vibrio alginolyticus. The absence of lrp significantly enhanced swarming motility, biofilm formation, extracellular protease secretion activity, and tolerance to copper ions. Meanwhile, the cumulative mortality of zebrafish (Danio rerio) was challenged by intraperitoneal injection against the lrp mutant strain reached 68.89%, significantly higher than that of the wild-type strain by 40.00%. Additionally, the expression levels of lrp showed a gradual decrease with increasing culture time when affected by different physicochemical factors. In the early-log phase, the expression level of lrp was significantly induced by pH 5, 22°C, 5% NaCl, 1/4/7 mM ferric citrate, 0.1/5 mg/L NaNO3, and 0.1 mg/L KH2PO4. And the mRNA level of lrp was significantly decreased at the mid-log phase by 1% and 5% NaCl. When cultivation arrived at the late-log phase of growth, pH 5, 1 mM Cu2+, 1 mM ferric citrate, and 5 mg/L NaNO3 increased the expression of lrp while 37℃ inhibited its expression. Overall, these works indicate that lrp negatively controls the virulence of V. alginolyticus probably by reducing bacterial swarming motility, biofilm formation, extracellular protease secretion activity, and tolerance to copper ions, and its expression is affected by diverse physicochemical factors, especially it is mainly up-regulated in the early logarithmic stage of bacterial growth.